The Increase of Child Labour in Nigeria: Legal Custody of Victim by the Nigerian Government as a Panacea - Aidonojie, Paul Atagamen; Obieshi, Eregbuonye; Aidonojie, Esther Chetachukwu; Hassan, Ismaila; Damina, Joshua John (Journal of Indonesian Constitutional Law, 2024)
It is apt to state that there are numerous rights and obligations guardians or parents owe to their children or children in their custody. Although several laws seem to secure the right of children against child labour in Nigeria, however, it has been observed that there has been a recurrent increase in child labour, which is becoming a major challenge truncating the features of most children. In this regard, this study adopts a hybrid method of research in ascertaining if the Nigerian government takes custody of a child experiencing child labour could aid in curtailing the major challenge of child labour. In this regard, the study employs an online questionnaire sent to 307 respondents who reside in Nigeria. The study, therefore, found that, though several international and local laws tend to discourage child labour in Nigeria, there is still an increase in child labour. The study further found that several factors are often the root causes of child labour, and third-party custody of children suffering from child labour is a better solution. The study, therefore, concluded and recommended that to curb the major challenge of child labour, the Nigerian government needs to take a proactive step in assuming custody of children experiencing child labour. Hence, this study contributes to knowledge by determining if third-party custody is a possible consideration by the Nigerian government in legal-social intervention regarding diminished child labour and enforcing gaps left in existing child protection structures.